2020
DOI: 10.1590/1809-4422asoc20190049r2vu2020l6ao
|View full text |Cite
|
Sign up to set email alerts
|

“All That’s Left is Bare Land and Sky”: Palm Oil Culture and Socioenvironmental Impacts on a Tembé Indigenous Territory in the Brazilian Amazon

Abstract: The expansion of large-scale oil palm cultivation in the Amazon has exposed indigenous populations to changes around their lands and in their daily activities. Given the lack of studies on the impacts of oil palm on these populations, this study analyzed the socio-environmental impacts perceived by the Tembé, in Tomé-Açu, Pará State. With an interdisciplinary approach, between 2016 and 2017, semi-structured interviews and participant observation were conducted in five villages, inside and adjacent to the Turé-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Within the literature on sociopolitical and sustainability aspects of oil palm associated with water (16 papers), we found a few examples that conduct a comprehensive analysis of community perceptions on water-related issues linked to oil palm cultivation (a total of four papers). Available studies use structured or semi-structured interviews with different stakeholders (including indigenous groups, smallholders, government officials, and private sector organizations) to identify positive and negative effects of oil palm cultivation and expansion on environmental and socio-economic conditions of local communities (Larsen et al 2014, Tittor 2017, Damiani et al 2020, Hervas 2020. Additionally, we found two studies, classified in the fluvial processes category, that use interviews with villagers and instrument data to empirically validate the communities' perceptions of water issues (Merten et al 2016(Merten et al , 2020.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Within the literature on sociopolitical and sustainability aspects of oil palm associated with water (16 papers), we found a few examples that conduct a comprehensive analysis of community perceptions on water-related issues linked to oil palm cultivation (a total of four papers). Available studies use structured or semi-structured interviews with different stakeholders (including indigenous groups, smallholders, government officials, and private sector organizations) to identify positive and negative effects of oil palm cultivation and expansion on environmental and socio-economic conditions of local communities (Larsen et al 2014, Tittor 2017, Damiani et al 2020, Hervas 2020. Additionally, we found two studies, classified in the fluvial processes category, that use interviews with villagers and instrument data to empirically validate the communities' perceptions of water issues (Merten et al 2016(Merten et al , 2020.…”
Section: Resultsmentioning
confidence: 98%
“…We found several studies comparing changes or evaluating soil properties in forests and oil palm(Nelson et al 2014, Allen et al 2015, Sumarga et al 2016, Kenye et al 2019, Khasanah and van Noordwijk 2019, Swails et al 2019, Merten et al 2020), agroforest usually involving rubber (Bruun et al 2013, Couwenberg and Hooijer 2013, Allen et al 2015, Guillaume et al 2016, Hermawan et al 2019, Kenye et al 2019, Khasanah and van Noordwijk 2019,Merten et al 2020), and few studies evaluating changes in soils due to the transition from pastures(Nelson et al 2014, Goodrick et al 2015, Quezada et al 2019. We also found literature addressing the impact of different management practices such as using various understory vegetation(Satriawan et al 2016, Wawan et al 2019, Rahman et al 2021 and enhancing infiltration rates(Tarigan et al 2016, Damiani et al 2020.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Bourdieu wanted to overcome the dualism of structure and agency and think about practice in a truly relational way (de Moll & Betz, 2016). Basically, the socio-cultural reproduction of society is a form of response to changes that occur in society (Damiani et al, 2020). Support from outsiders becomes a form of legitimacy for cultural reproduction (Rossolatos, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Colchester (2007), Colchester et al (2010), Nilakrisna et al (2016), Prasetijo (2017), Sager (2008), Steinebach (2013), Rahayu et al (2021), and Sirait (2009) were conducted in Sumatra and West Kalimantan and found similar results. Additionally, Huesca (2016), Pichler (2013), Colchester et al (2010), Kadiri (2021), andDamiani et al (2020) conducted related studies in Brazil, Nigeria, and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%